Influence of the maximum force indicators on the efficiency of passing the distance in academic rowing - Strykalenko, Y.; Shalar, O.; Huzar, V.; Andrieieva, R.; Zhosan, I.; Bazylyev, S. (Journal of Physical Education and Sport, 2019)
In modern sport, achievement of good results can only be justified in the well-founded scientific approach to build a training process. Aim: to determine the relationship between the indicators of the maximum strength of the rowers and the efficiency of passing the distance in academic rowing. Materials and methods: the research was conducted on the basis of Kherson School of Higher Sporting Skill. Fifteen academic rowers participated in the experimental part. All participants of the research had high sports qualification: Candidate for Masters of Sports (CMS), Master of Sports (MS), Master of Sports of the International Class (MSIC) and Honored Master of Sports (HMS). Methods of studying strength and functional readiness included the testing of the physical qualities of high sports qualification academic rowers, namely: pull the barbell with the hands lying down, the maximum acceleration on the paddle ergometer `Concept-2` `Dyba`, horizontal traction in the block simulator (full amplitude) and the control test on the `Concept-2` rowing simulator on a sports distance of 2000 m. Results: during the research, a significant correlation link between the sporting result (rowing 2000 m) and the indicator of `maximum acceleration on the paddle `Concept-2` simulator was determined, where r=0,754, testifying the effect of this indicator on the efficiency of passing the distance in academic rowing. The correlation link between the maximum acceleration on the paddle ergometer and the force tests have been established experimentally: the traction of the lying down (r = - 0,643) and the traction on the `Dyba` (r = - 0,844). Conclusions: during the planning of training work, trainers need to pay significant attention to the development of strength endurance, but also they must take into account the close relationship between the time of passage of the distance and the indicators of maximum strength of athletes. Only due to the rational planning of training loads it is possible to achieve maximum results in competitions of the highest level.